Le verre de Sabra al-Mansuriya (Kairouan, Tunisie) milieu Xe - milieu XIe siècle : production et consommation : vaisselle - contenants - vitrages - Foy, Danièle 1951-; Freestone, Ian 19XX- (Archaeopress Publishing Ltd., 2020)
Knowledge of Islamic glass and its craftsmanship in the medieval period has relied heavily on Middle Eastern literature. The study of workshop and rich glass assemblage from Sabra al-Mansuriya (Kairouan), the Fatimid capital founded in 947/948 and destroyed in 1057, shows that Ifriqiya followed the technological evolutions of glass craftsmanship
Keywords: Islam; Glas; Ausgrabung; Kairuan; Islamic glassware / Tunisia / Qayrawān; Glassware, Medieval / Tunisia / Qayrawān; Excavations (Archaeology) / Tunisia / Qayrawān; Archaeology, Medieval / Tunisia / Qayrawān; Qayrawān (Tunisia) / Antiquities